Dissecting the THz spectrum of liquid water from first principles via correlations in time and space - Heyden, Matthias; Sun, Jian; Funkner, Stefan; Mathias, Gerald; Forbert, Harald; Havenith, Martina; Marx, Dominik; Klein, Michael L. (Proceedings of the National Academy of Sciences - PNAS, 2010)
Solvation of molecules in water is at the heart of a myriad of molecular phenomena and of crucial importance to understanding such diverse issues as chemical reactivity or biomolecular function. Complementing well-established approaches, it has been shown that laser spectroscopy in the THz frequency domain offers new insights into hydration from small solutes to proteins. Upon introducing spatially-resolved analyses of the absorption cross section by simulations, the sensitivity of THz spectroscopy is traced back to characteristic distance-dependent modulations of absorption intensities for bulk water. The prominent peak at≈200 cm⁻¹ is dominated by first-shell dynamics, whereas a concerted motion involving the second solvation shell contributes most significantly to the absorption at about 80 cm⁻¹ ≈2.4 THz. The latter can be understood in terms of an umbrella-like motion of two hydrogen-bonded tetrahedra along the connecting hydrogen bond axis. Thus, a modification of the hydrogen bond network, e.g., due to the presence of a solute, is expected to affect vibrational motion and THz absorption intensity at least on a length scale that corresponds to two layers of solvating water molecules. This result provides a molecular mechanism explaining the experimentally determined sensitivity of absorption changes in the THz domain in terms of distinct, solute-induced dynamical properties in solvation shells of (bio)molecules—even in the absence of well-defined resonances.